ADOPSI DALAM PERSPEKTIF HUKUM ISLAM - Abu Alim (Constitutum: Jurnal Ilmiah Hukum, 2023)
The phenomenon of adoption has become commonplace in various parts of the world because it is a step for almost all families (husband and wife) who have not been blessed with children by Allah SWT after several years of marriage. Especially for those who are Muslim, they must really pay attention to the steps and decisions they take, whether they are in accordance with the values of Islamic law or not? This is intended so that the decision to adopt a child is not just a desire to have children, but also in accordance with existing Islamic law, in order to balance happiness in this world with happiness in the afterlife. The aim of this research is to clearly describe the status and position of child adoption in the perspective of Islamic law. Is there actually an adoption in Islam? This research method is normative juridical using secondary data in the form of regulations, books, journals and other scientific works. Adoption can be carried out on condition that the adopted child and the adoptive parents have a bond of mutual friendship (mahram), such as adopting a daughter from a brother and so on, a son or grandson from a brother or sister from the same father or mother and so on in a straight line downwards. Adoption can also be done by non-mahram people, this is better understood from an Islamic legal perspective with the term hadhanah.